Drug Resistance of Candida Species Isolated from Fungal Peritonitis by PCR-RFLP Method - M Alinejad (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Fungal peritonitis is a relatively rare disease with serious complications in peritoneal dialysis patients and is associated with significant morbidity and mortality. Candida species are the most common cause of fungal peritonitis. The objective of this study was to isolate the Candida species in the patients with peritoneal dialysis by molecular methods, and thus to determine their drug resistance. METHODS: In this cross-sectional study, sampling (peritoneal samples) was carried out on 210 suspicious patients with peritonitis after peritoneal dialysis in Tehran, Iran in 2010. Species identification was done by direct microscopic tests, culture on Chromagar and Corn meal agar, Germ tube test in bovine serum, Urease test, and biochemical identification with the API 20 kit. Identification of isolated yeasts was confirmed by PCR-RELF method. Antifungal susceptibility testing of isolated Candida species was conducted by the broth dilution method in accordance with the National Committee on Clinical Laboratory Standards guidelines [NCCLS-M27]. FINDINGS: Totally 210 samples were surveyed that 40 cases (19.05%) with microbial peritonitis were identified based on experiments, which only 9 cases (22.5%) had Candida peritonitis which determined as specific species in accordance with PCR-RFLP molecular technique for confirming phenotyping methods. Among these 9 cases of isolated candida species, 5 cases of them (55%) were C. albicans, 1 case (11%) was C. Kefyr and 2 cases (22%) were C. guilliermondii and also 1 case (11%) was C. parapsilosis. The MIC determined by antifungal susceptibility testing were: C. albicans (Amphotericin B=0.125 µg/ml, Fluconazole=2 µg/ml, 5- Flucytosine=2 µg/ml), C. guilliermondii (Amph B=1 µg/ml Flu=2 µg/ml, 5- Fluc=4 µg/ml), C. Kefyr (Amph B=0.5-1 µg/ml, Flu=0.5- 1 µg/ml, 5- Fluc=2-4 µg/ml) and C. parapsilosis (Amph B =0.5 µg/ml, Flu =1 µg/ml, 5- Fluc=0.5g/ml).CONCLUSION: Accurate identification of Candida albicans and non-Candida albicans species cases of Candida peritonitis in patients with peritoneal dialysis is necessary.